Coroa, igreja e ciência: a alternância da dinâmica administrativa da Coroa Portuguesa nos sertões do Piauí do século XVIII = Alternativtitel: Crown, Church and science : Alternation of the administrative dynamics of the Crown in the backlands of Piauí - Araújo, Pedrina Nunes (Plura, revista de estudos de religião, 2025)
During the 18th century, the Portuguese Crown incorporated a logic of knowledge production linked to the Enlightenment ideal and, based on this logic, executed the administration of its colonial territories. This global dynamic was observed in the local context from the creation of the captaincy of Piauí. However, in an earlier period, the participation of the bishops had already established itself in an important way in the process of conquest and construction of the colonial territory of Piauí. The most obvious example of this fact highlights the performance of D. Frei Manuel da Cruz, who was responsible for providing for most of the parishes in the territory, as well as establishing direct contact with the populations when he made pastoral visits to the backlands, collecting as much information as possible about the places he passed through. This example cited demonstrates how the Church was used by the Portuguese administration to carry out this type of work. However, this dynamic changed when Portugal decided to enter the network of science and knowledge production, building a more illustrated type of royal administration. Thus, this article aims to demonstrate how the alternation of administrative posture occurred in the eastern territory of the State of Maranhão and Grão-Pará, and began to be executed when, in 1758, King D. José I decided to create the Captaincy of Piauí. With this, the Crown used the knowledge acquired to build villages, delimit borders, elaborate a cartographic knowledge of the region, get to know the nature and dispose of the position of the bishopric of Maranhão linked to the logic of State.